(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
We would have to consider the issue in terms of the complete system of moral principles and the socioeconomic makeup of society, which is something we cannot do. Criminal behaviour on the part of a public worker while performing his duties is defined under Section 5 of the Prevention of Corruption Act, 1947. The inability of government programmes to successfully address the issues they were intended to have been caused by corruption in the implementation of developmental schemes for the elevation of the impoverished and destitute parts of society. In some areas of India, corruption has become such a pervasive aspect of government and business that nothing gets done without greasiness on the part of the bearer. The presence of corruption involves the existence of corrupt individuals, corrupt behaviours, and a corrupt system. The issue of corruption in India as well as in West Bengal, has major repercussions for upholding the rule of law and ensuring access to justice.